The use of games in the teaching of Production Engineering: a list based on publications in Scopus - Machado, Bruna Andrade [UNESP]; Hotta, Bárbara Yumi [UNESP]; Garcia, Gabriel Lino [UNESP]; de Souza, Fernando Bernardi [UNESP]; de Souza Rodrigues, José [UNESP] (My University, 2022)
The use of games in the teaching of production engineering is on the rise since it allows the presentation of knowledge and its absorption in a more relaxed way, it helps the development of essential skills for a good professional as well. As a way of identifying educational games developed, used and/or published in production engineering courses, a qualitative research was carried out on the Scopus database. The research returned 40 publications, of which 11 could not be accessed and only 18 had games related to the course in question. As a result, 44 games were compiled, which were listed in order to facilitate their knowledge by teachers in the area, stimulating their application and the modernization of teaching.
Keywords: Educational Games; Game List; Game-based Learning; Production Engineering